Marketing to healthy lifestyle consumers: An analysis of demographic and social cognitive factors - Yap, Sheau Fen; Othman, Md Nor (College of Management, National Cheng Kung University, 2010)
Individuals who adopt a healthy lifestyle are excellent customers for health-related offerings. The present study represents the first attempt to examine group differences between "high active" and "low active" exercisers in demographic and social cognitive characteristics which aims to provide useful insights to marketers in segmenting markets, targeting promotions, and positioning products and services. Cross-sectional data was collected via self-administered surveys from general adults sample (n = 512) in Malaysia. Prior to data analysis, measurement scale was validated using confirmatory factor analysis. Significant differences were found between the two exercise groups in age, occupation and all the social cognitive factors studied. The "low active" group had less favourable instrumental and affective attitude, were less subject to social pressure, and felt less perceived control and self-efficacy over exercising compared to "high active" exercisers. The discriminant analysis reported perceived self-efficacy to be the most important factor in discriminating between the two groups.